The Impact of the Existence of Renon Field as a Public Open Space on the Value of the Surrounding Land - Vianthi, Ni Putu Yunita Laura; Suartika, Gusti Ayu Made (ASTONJADRO, 2025)
Fields or parks in the city center as public open spaces have social functions, ecological functions, environmental functions and economic functions. In terms of economic function, its existence has an impact as a movement of regional economic development. Fields that are strategically located in the core of the city center of government will affect the development of land use around them. As a result, this will have implications for increasing the need for land, which will ultimately escalate the economic value of the land. This study aims to analyze the impact of the existence of Renon Field as a public open space on the economic value of the land around it. The method used is a descriptive and comparative quantitative approach. The study used a comparison test of the difference between two areas, namely the subject area (Jl. Raya Puputan) as the affected area and the control area (Jl. Cok. Agung Tresna and Jl. Moh. Yamin) as a controlled area/considered not affected. Thus, the results obtained show that the existence of the Renon Field has a real impact with the acquisition of land value results in the subject area (Jl. Raya Puputan) being greater and/or having a significant difference in land value compared to the land value in the control area (Jl. Cok. Agung Tresna and Jl. Moh Yamin) as a corridor that is considered unaffected.